Epithelial cell–derived prostaglandin D2 inhibits chronic allergic lung inflammation in mice. Issue 7 (24th April 2019) - Maehara, Toko; Nakamura, Tatsuro; Maeda, Shingo; Aritake, Kosuke; Nakamura, Masataka; Murata, Takahisa
ABSTRACT: The precise role of prostaglandin D (PGD)2 in allergic lung inflammation remains controversial. Here, we aimed to clarify the role of PGD2 in chronic allergic lung inflammation using hematopoietic PGD synthase (H‐PGDS)–deficient mice. Repeated intranasal administration of ovalbumin (OVA) resulted in eosinophilic infiltration and mucin production in the lungs of wild type (WT) mice, leading to respiratory dysfunction. H‐PGDS deficiency exacerbated these effects, which were accompanied by increased mRNA expression of TNF‐α and eosinophil chemoattractants. The bronchial epithelium expressed both H‐PGDS and TNF‐α in the inflamed WT lung, and H‐PGDS deficiency increased TNF‐α expression further. In cultured bronchial tissue of WT mice, treatment with LPS elevated mRNA expression of TNF‐α and eosinophil chemoattractants. H‐PGDS deficiency promoted the expression of these factors, which was inhibited by treatment with PGD2 receptor, D prostanoid (DP) receptor agonist, or PGD2 metabolite 15‐deoxy‐Δ 12, 14 ‐PGJ2 (15d‐PGJ2 ). Treatment with TNF‐α receptor antibody inhibited eosinophil chemoattractant expression. In vivo, administration of DP agonist or 15d‐PGJ2 inhibited OVA‐induced allergic lung inflammation. Bronchial epithelial cell–derived PGD2 attenuated lung eosinophilic infiltration with chronic allergic inflammation; these phenomena are at least partly attributed to the inhibition of TNF‐α production via DP activation or 15‐deoxy‐Δ 12, 14 ‐PGJ2 signaling.—Maehara, T., Nakamura, T., Maeda, S., Aritake, K., Nakamura, M., Murata, T. Epithelial cell–derived prostaglandin D2 inhibits chronic allergic lung inflammation in mice. FASEB J. 33, 8202–8210 (2019). www.fasebj.org